Missing the Forest and the Trees: Lost Opportunities for Federal Land Exchanges - Miller, Scott K. (Columbia Journal of Environmental Law, 2019)
For any land exchange carried out by the Forest Service or the Bureau of Land Management (“Agencies”), federal law generally requires the Agencies to ensure that “the public interest will be well served by making that exchange.” To do so, the Agencies must consider the fate of the land they convey and how that is likely to affect the public interest. To help control the fate of the land they convey and the adverse impacts it may have on the public interest, the Agencies’ regulations mandate that they “reserve such rights or retain such interests as are needed to protect the public interest.” Nevertheless, the Agencies’ internal policies all but prohibit their employees from carrying out that mandate. As a result, the Agencies are missing opportunities to better serve both the public’s interests and their own. By including covenants, easements, or other restrictions on the lands they convey, the Agencies can more accurately and confidently determine the future use of the land. Doing so can have substantial benefits not only for the public interest, but also for the efficiency and defensibility of the Agencies’ land exchange processes. A new policy is necessary, and its lessons will have broader applicability to dozens of federal agencies and the billions of dollars of real property transactions in which they engage. This Article begins with a short case study that starkly illustrates the Agencies’ practices and their significant shortcomings. Following the case study, the Prologue continues with a more thorough introduction to the subject and the thesis that is explored. Parts II and III describe the prominent features of the physical and historic landscape within which the Agencies’ land exchange programs operate—including the Agencies’ land management imperatives and their public interest lapses—while Parts IV and V explore the statutory, regulatory, and judicial landscape. The discussion demonstrates the significant responsibilities the Agencies have to guide the future use of the land they convey when necessary to serve the public interest. Part VI explores the substantial transactional and opportunity benefits the Agencies miss by failing to consider and strategically employ restrictions on the lands they convey, and Part VII critiques the Agencies’ arguments that have led to these missed opportunities. Finally, this Article suggests a framework for developing new policies that will better serve the Agencies and the public.